Illumina-Based Analysis Yields New Insights Into the Fungal Contamination Associated With the Processed Products of Crataegi Fructus - Yu, Jingsheng; Guo, Mengyue; Jiang, Wenjun; Dao, Yujie; Pang, Xiaohui (Frontiers in Nutrition, 2022)
Crataegi Fructus, a medicinal and edible herb in China, has been considered as a popular dietary supplement globally. It is used for the treatment of dyspepsia and chronic heart failure according to the Chinese Pharmacopoeia (2020). However, the fungal contamination in Crataegi Fructus affects its quality and safety, thus preventing its global promotion. In the present study, we comprehensively studied the fungal community in the processed products of Crataegi Fructus through high-throughput sequencing. A total of 21 Crataegi Fructus samples were collected from five provinces in China, and the samples were divided into five groups based on collection areas, as well as three groups based on processing methods. We then targeted the internal transcribed spacer 2 sequence through the Illumina Miseq PE300 platform to investigate the fungal composition and diversity. Results showed that all the 21 samples were detected with fungal contamination, and Ascomycota was dominant at the phylum level. In the groups based on collection areas, Dothideomycetes, Pleosporaceae, and Alternaria were dominant at the class, family, and genus level, respectively. In the groups based on processed methods, Dothideomycetes, Aspergillaceae, and Alternaria were the most abundant at the class, family, and genus level, respectively. The differences of fungal communities between various groups were also observed. Furthermore, a total of 115 species were identified, among which seven species were potential toxigenic, namely Trichothecium roseum, Alternaria tenuissima, Aspergillus carbonarius, Penicillium brevicompactum, Aspergillus fumigatus, Rhizopus microspores, and Pichia fermentans. In conclusion, this work reveals great fungal richness and diversity in Crataegi Fructus, providing references for the prevention and control of fungal contamination of Crataegi Fructus in practical production.